Kewenangan Pemerintah Menerapkan Sanksi terhadap Pelaku Distorsi Pasar Berdasar Maqasid al-Syari’ah
The act of speculators distorting the market is quite unsettling. However, the Sharia texts show that this problem can be resolved using moral or akhlÄqÄ«. Then the question is whether the present government can overcome it by using qadÄ'Ä«e imposing sanctions for distortion. Since the nature of Sharia is the universal and eternal, this issue must be answered comprehensively and holistically. For that reason, the maqÄsid approach is operated with istislÄhiyyah method. This method is also referred to as al-ijtihÄd al-maqÄs